Rekomendasi Hunian KPR Subsidi Terbaik dengan Metode SMART(Simple Multi Attribute Rating Technique) - Saleh, Albi (LPPM UNIKA Santo Thomas Medan, 2022)
This research was conducted to process recommendations in determining subsidized housing (KPR) for people who incidentally have low incomes using the SMART (Simple Multi Attribute Rating Technique) method in the Sukabumi City area. The research method uses SDLC (Software Development Life Cycle), with data collection techniques namely observation, interviews and literature study. The result of this research is a subsidized housing recommendation system using the SMART method which has an impact on time efficiency and becomes a reference for people who want to have a mortgage house.